Juridical Analysis of Marriage Laws and Regulations in Indonesia and the United Kingdom - Putra, Gilar Giri Prayoga; Febryliani , Nandhita; Najmadina , Adisha; Gunawan , Moh.Sigit; Permana , Deni Yusup (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the comparative juridical marriage laws and regulations system in Indonesia and the United Kingdom. Using a normative juridical method, this study examines the differences in philosophical foundations, marriage implementation procedures, registration systems, divorce provisions, and legal norms that apply in both countries. The study results show that there are fundamental differences in the marriage legal system of the two countries, where Indonesia adheres to a system that is thick with religious and pluralistic values. At the same time, the United Kingdom applies a secular and liberal approach. This difference can be seen in the regulation of marriage age limits, polygamy, same-sex marriage, and interfaith marriage. Indonesia's marriage registration system adheres to dualism with the Office of Religious Affairs for Muslims and Civil Registration for non-Muslims. At the same time, the UK has an integrated registration system through the General Register Office. Divorce procedures in Indonesia still distinguish between talaq divorce and lawsuit divorce with specific ground requirements, while the UK has implemented a no-fault divorce system. This study identifies challenges in harmonizing marriage laws due to globalization, especially related to the recognition of marriage across jurisdictions. To create legal certainty for cross-border marriages, a holistic approach and the development of a comprehensive international legal framework are needed.